A dimensional approach to assessing delirium in COVID-19 in the elderly - V. E. Pashkovskiy; N. N. Petrova; M. S. Sivashova; A. Ya. Vuks; G. A. Prokopovich (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The aim of the study was to investigate the structure of delirium in elderly patients with different outcomes of coronavirus infection.Materials and Methods. The study was carried out on the basis of Hospital for War Veterans, St. Petersburg. The study involved  30 patients: 13 male and 17 female (median age (Med) 70.5, interquartile range (IQR) 62-83) with clinical diagnosis: "New coronavirus infection COVID-19 (PCR+), F05.86 other delirium in association with other viral and bacterial neuroinfections. Peculiarities of delirium manifestations were studied using Delirium Rating Scale-Revised-98 (DRS-R-98). Current physical condition was monitored using The National Early Warning Score (NEWS2) for COVID-19.Results: All patients had moderate to severe disorders of the wake-sleep cycle on the DRS-R-98 scale. In addition, perceptual and long-term memory impairments were common. A significant correlation (p<0.05) was found between the severity of the physical condition and disorders of the sleep-wake cycle, lability of affect, formal thought disorders, motor agitation, and disorientation. In addition, there were significant correlations (p<0.05) between delirium symptoms and physical status scores on the NEWS2 scale. In lethal patients, more pronounced disturbances were recorded on sleep-wake indicators (Med.3.0, IQR 2.0-3.0 vs Med.2.0, IQR 2.0-3.0, p=0.0327) and motor agitation (Med.2.0, IQR 1.0-2.5 vs Med.1.0, IQR 0.0-2.0, p=0.441). A logit regression model showed that the variables "respiratory rate," "heart rate," and the final NEWS2 score could be considered predictors of disease outcome.Conclusion. Delirium, one of the most frequent manifestations of acute brain dysfunction, is a serious complication of COID-19 in hospitalized patients and a strong predictor of adverse outcome of coronavirus infection in older patients.